A low-cost bipolar pulse generator for high-frequency ultrasound applications - Xu, Xiaochen (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2007)
A design of a low-cost bipolar pulse generator for high-frequency (HF) ultrasound applications is presented. The pulse generator can produce N cycle (1-255 cycles) bipolar pulses with center frequency over 60 MHz. The measured pulse amplitude was over 160 Vpp, and the pulse ringing was less than 0.3 Vpp (i.e., signal-to-ring ratio is 55 dB). The pulser can be used in high-frequency ultrasound Doppler and B-mode imaging applications with arrays